Factors Influencing The Purchase Intention in Online Organic Fruit and Vegetable Stores - Nur Adhita Rahmawati; Arif Imam Suroso; Arief Ramadhan (School of Business, Bogor Agricultural University (SB-IPB), 2018)
The increasing number of organic agricultural production and public awareness toward healthy living provide the opportunities in trading for the products itself. Meanwhile, the development of information technology produces innovation such as electronic commerce (e-commerce), and in agribusiness, it is known as e-agribusiness. E-agribusiness allows organic groceries trade activities to be conducted online through a website. However, that is a new and rare activity in Indonesia, therefore the management of company needs to develop the strategy to enhance the customers and survive in the industry. The purpose of this study is to analyze the factors influencing organic fruit and vegetable purchase intention through a website based on technology perspective and consumer behavior. WebQual and Theory of Planned Behavior (TPB) were used in this study. This study was conducted on website of Sayur Box, one of e-agribusiness in Indonesia. Face-to-face survey technique was used to collect the data from 113 respondents. PLS-SEM was used for data analysis. The result shows that online purchase intention is affected by attitude and perceived behavioral control. All of WebQual’s instruments that used in this study affect user satisfaction toward the website except for the usefulness variable. User satisfaction toward the website has an indirect effect on online purchase intention through attitude variable.Keywords: e-agribusiness, online purchase intention, structural equation modeling, theory of planned behavior, website quality